Non-small cell lung cancer and metabolism research from 2013 to 2023: a visual analysis and bibliometric study - Yang, Jin; Yang, Wei; Zhang, Jie; Huang, Aiping; Yin, Shiyuan; Zhang, Hua; Luo, Zongrui; Li, Xiaojuan; Chen, Yihua; Ma, Lijie; Wang, Chao (Frontiers in Oncology, 2024)
Background As one of the most prevalent primary lung tumors, non-small cell lung cancer (NSCLC) has garnered considerable research interest due to its high metastasis rates and poor prognosis outcomes. Across different cancer types, metabolic processes are required for tumors progression and growth, thus interfering with such processes in NSCLC may therapeutically viable for limiting/halting disease progression. Therefore, comprehending how metabolic processes contribute to growth and survival mechanisms in cancers, including NSCLC, may elucidate key functions underpinning tumor cell metabolism. However, no bibliometric analyses have been published in this field, therefore we address this knowledge gap here. Methods Between 2013 and 2023 (December 28th), articles related to the NSCLC and metabolism (NSCLC-Met) field were retrieved from the Web of Science Core Collection (WoSCC). To fully dissect NSCLC-Met research directions and articles, we used the Bibliometrix package in R, VOSviewer and CiteSpace software to visually represent global trends and hotspots. Results Between 2013 and 2023, 2,246 NSCLC-Met articles were retrieved, with a continuous upward trend and rapid development observed year on year. Cancers published the most articles, with Cancer Research recording the highest average citation numbers. Zhang Li from China was the most prolific author, but the highest number of authors came from the USA. China, USA, and Italy were the top three countries with the highest number of published articles, with close cooperation identified between countries. Recent hotspots and research directions were reflected by “lung adenocarcinoma”, “immunotherapy”, “nivolumab”, “checkpoint inhibitors”, “blockade”, and “pembrolizumab”, while “gut microbiome”, “egfr” and “dose painting” were important topics for researchers. Conclusion From our analyses, scientists can now explore new hotspots and research directions in the NSCLC-Met field. Further in-depth research in this field will undoubtedly provide more new insights on disease diagnostics, treatment, and prognostics.